URBAN SPRAWL OF THE CITY OF YOGYAKARTA, SPECIAL REFERENCE TO THE STAGE OF SPATIAL TRANSFORMATION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The study was conducted in Maguwoharjo Village, Depok Sub-District, Sleman District, which is part of urban fringe area experiencing regional transformation. This study aims at understanding the regional transformation stages in the location studied The survey method using in-depth interviews with some informants was implemented. The data analysis was done descriptive qualitatively. From this study, it is found out that spatial distribution of regional transformation stages is closely associated with street connection and growth areas. Some areas directly bordering on Yogyakarta-Surakarta roads have higher regional transformation intensity than villages distant from the streets and growth areas.